E-Business development and the factors affecting of its application in hospitality operations sustainability - Ibrahim, Irwan; Ismail, Albert Feisal @ Muhd Feisal; Amer, Afizan; Baharuddin, Farrah Nadia; Feisal, Albert (International Research Association for Talent Development and Excellence, 2020)
Digital technology has become an essential catalyze for the tourism industry. Digital technology played a significant role in shifting the tourism sector into an impact driven industry. Factors affecting the usage of E-business in the tourism industry have been well-documented in developed countries, but further studies are needed to investigate the usage of E-business in the tourism industry among developing countries. This study aims to identify the level of E-business usage as well as the benefits and barriers of E-business adoption in hospitality operation sustainability among local tourism agencies operating in Melaka. The E-Business Measurement Evolution Model and the quantitative approached was applied for this study. Questionnaires were distributed to the respondents in the form of an online and self-administered questionnaire. Statistical Package for Social Science (SPSS) version 25.0 was used to analyze the data. The research findings revealed that tourism agencies in Malacca were still in the early stages of E-business usage, with only (54%) of the travel agencies are online. The factor of saving time (M = 4.3492) was the key benefit in E-business usage while the factor of hackers’ intervention (M = 3.8730) was revealed to be the most deterring factor that causes the tourism agencies reluctance to adopt E-business practice. This study shows that government aims of E-business tourism have not been fully realized. The respondents still perceive the factors of internet fraud and security are a significant issue for E-business usage. Therefore, future research is recommended to provide more insights into the application of E-business tourism in tandem with the government aim of the hospitality operations sustainability Malaysian tourism industry.